2019
DOI: 10.4172/neuropsychiatry.1000564
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories of Treatment Response in Hallucinations

Abstract: ObjectiveHallucinations are highly prevalent in schizophrenia and related disorders. Antipsychotics are generally effective in treating hallucinations, but major inter-individual differences in treatment response exist. Previous studies have identified heterogeneity of over-all antipsychotic response patterns in schizophrenia. The aim of this study was to explore the heterogeneity in the response of hallucinations to antipsychotic drug treatment in a representative sample of patients acutely admitted for psych… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 39 publications
1
3
0
Order By: Relevance
“…For participants with clinically significant hallucinations, the symptom had decreased to “mild” according to PANSS P3 after 3 weeks and continued to decrease throughout the follow-up period. This finding is consistent with our previous findings, where 80% of patients with clinically significant hallucinations at baseline were found to be “dramatic” responders, with extinction of hallucinations during the first 4 weeks of treatment 11 . The present results are also in line with findings from Sommer et al 10 where first-episode schizophrenia patients showed a mean reduction of hallucinations from 4.4 at baseline to 2.5 after 4 weeks of treatment measured by the PANSS P3 item.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…For participants with clinically significant hallucinations, the symptom had decreased to “mild” according to PANSS P3 after 3 weeks and continued to decrease throughout the follow-up period. This finding is consistent with our previous findings, where 80% of patients with clinically significant hallucinations at baseline were found to be “dramatic” responders, with extinction of hallucinations during the first 4 weeks of treatment 11 . The present results are also in line with findings from Sommer et al 10 where first-episode schizophrenia patients showed a mean reduction of hallucinations from 4.4 at baseline to 2.5 after 4 weeks of treatment measured by the PANSS P3 item.…”
Section: Discussionsupporting
confidence: 94%
“…Hallucinations in general and auditory verbal hallucinations in particular are important treatment targets, being not only a major burden to patients but might also lead to self-harm, suicide, violence or homicide 8,9 . Hallucinations respond well to antipsychotics, and the response is likely to appear rapidly 10,11 . In our previous study, we demonstrated that more than three-quarters of patients with clinically significant hallucinations at baseline reported vanishing of hallucinations during the first 4 weeks of treatment 11 .…”
mentioning
confidence: 90%
See 2 more Smart Citations